Public Flats for the Poor? Legal Review of Cingised Rusunawa’s Effectiveness in Bandung - Alega, Alega; Hadimulyo, Joshua (Universitas Negeri Semarang, 2025)
Rapid population growth and limited land in urban areas have encouraged the government to develop vertical housing solutions such as Simple Rental Flats (Rusunawa), one of which is Rusunawa Cingised in Bandung City. The presence of Rusunawa aims to provide decent, safe, and affordable housing for Low-Income Communities (MBR), as well as being part of the city planning strategy, but its implementation in the field still causes various problems, both from legal, social, economic, and technical management aspects. This study aims to explain the legal provisions regarding Rusunawa and examine the effectiveness of utilizing Rusunawa Cingised as a solution for providing housing for MBR. The research method used is normative legal research with a qualitative approach through literature studies, based on secondary data from laws and regulations, books, journals, and related documents. The results of the study show that legally the development of Rusunawa has been supported by various regulations, especially Law Number 20 of 2011 concerning Flats. In practice, Rusunawa Cingised has also made a significant contribution in providing affordable alternative housing amidst limited urban land. However, in terms of the effectiveness of its utilization, Rusunawa Cingised still faces obstacles, although social programs have been designed, implementation in the field has not been fully optimal, both in terms of infrastructure maintenance, resident involvement, and sustainability programs. Therefore, synergy is needed between legal policies, professional management, local government support, and active community participation in order to make Rusunawa an effective and sustainable housing solution for MBR in urban areas.